2020
DOI: 10.1029/2020gl090724
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Coastal Shoreline Modeling Using an Ensemble Kalman Filter to Include Nonstationarity in Future Wave Climates

Abstract: A novel approach to improve seasonal to interannual sandy shoreline predictions is presented, whereby model-free parameters can vary in time, adjusting to potential nonstationarity in the underlying model forcing. This is achieved by adopting a suitable data assimilation technique (dual state-parameter ensemble Kalman filter) within the established shoreline evolution model ShoreFor. The method is first tested and evaluated using synthetic scenarios, specifically designed to emulate a broad range of natural sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 43 publications
4
53
0
1
Order By: Relevance
“…This was also observed in previous studies, which showed that changes in wave regime can alter the model parameters and the functional relations between them (Ibaceta et al, 2020;Splinter et al, 2017). As a perspective of future work, one way to reduce the effects of model free parameters' uncertainties on modeled shoreline may be to employ non-stationary parameters that can adjust to changes in wave-climate regimes (Ibaceta et al, 2020). The use of non-stationary parameters would also imply a dynamic value of the r parameter, reducing uncertainties associated to the assumption of a linear relationship, between SF's response rate parameters.…”
Section: Model Free Parameterssupporting
confidence: 86%
“…This was also observed in previous studies, which showed that changes in wave regime can alter the model parameters and the functional relations between them (Ibaceta et al, 2020;Splinter et al, 2017). As a perspective of future work, one way to reduce the effects of model free parameters' uncertainties on modeled shoreline may be to employ non-stationary parameters that can adjust to changes in wave-climate regimes (Ibaceta et al, 2020). The use of non-stationary parameters would also imply a dynamic value of the r parameter, reducing uncertainties associated to the assumption of a linear relationship, between SF's response rate parameters.…”
Section: Model Free Parameterssupporting
confidence: 86%
“…More recently, aerial and camera photogrammetry and drone-derived datasets have been widely used e.g., [26][27][28][29]. Many approaches use modelling as a coastal monitoring tool e.g., [30,31]. Models can also be applied to evaluate areas prone to risk related to coastal processes e.g., [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to this single memory decay factor, model skill deteriorates considerably if multiple dominant forcing and beach response timescales are present (Vitousek et al, 2017;Almar et al, 2017;. Recent work by Splinter et al (2017) and Ibaceta et al (2020) also showed that timescales of beach change and forcing may be temporally dependent, with beaches undergoing rapid adjustment to the changes in the dominant wave forcing over time and where single memory decay models can fail to capture the observed shoreline signal.…”
Section: Discussionmentioning
confidence: 99%